Seismic Structural Analysis of the Alam-El Bueib Formation, Qasr Oil Field, North Western desert, Egypt - Metwalli, Farouk I; Yousif, Mahmoud S; Dally, Nancy H El; Ata, Ahmed S Abu El (Edelweiss Applied Science and Technology, 2019)
The Qasr oil and gas Field is located in the north western desert of Egypt. It belongs to the southeastern part of the Lower Jurassic-Cretaceous Shushan Basin. The Lower Cretaceous Alam-El Bueib formation composed of clastic rocks with noticeable carbonate proportions, and forms multiple oil-bearing sandstone reservoirs in Qasr field. The study aims to define and analyze the Surface and subsurface structural features which are a key issue in assessing reservoir quality. Through this integrated approach, one may be able to identify lithologies and fluids in this region and provide possibly new hydrocarbon fairways for exploration. For this purpose, seismic and well data were interpreted and mapped in order to visualize the subsurface structure of the Cretaceous section. Results show the effect of NE-SW, NW-SE, and E-W trending normal faulting on the Lower Cretaceous Alam-El Bueib formation and is extended to the Upper Cretaceous Abu Roash Formation. The effect of folding is minimal but can be detected. These normal faults are related to the extensional tectonics which affected the north western desert of Egypt during the Mesozoic. One reverse fault is detected in the eastern part and is related mostly to the inversion tectonics in the Late Mesozoic. The depth structure contour maps of the Alam-El Bueib horizons (AEB-1, AEB-3A, and AEB-3D) show several major normal faults trending NE-SW and minor normal faults trending NW-SE. One larger branching normal fault trending E-W and lies to the south of the study area. These step-normal faults divide the area into a number of tilted structural blocks which are shallower in the south and deepen to the north. The area of study was most probably affected by E-W trending normal faults during the opening of the Atlantic Ocean in the Jurassic. Later right-lateral compression resulted from the movement of Laurasia against North Africa, changed their trend into NE-SW faults with minor NW-SE trending folds. These compressive stresses are also responsible for the reverse faulting resulted by inversion in the Late Mesozoic.